2020
DOI: 10.3390/pathogens9100783
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Fungi in the Potable Water of Hospitals: A Public Health Threat

Abstract: Since the last decade, attention towards the occurrence of fungi in potable water has increased. Commensal and saprophytic microorganisms widely distributed in nature are also responsible for causing public health problems. Fungi can contaminate hospital environments, surviving and proliferating in moist and unsterile conditions. According to Italian regulations, the absence of fungi is not a mandatory parameter to define potable water, as a threshold value for the fungal occurrence has not been defined. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…According to previous studies [ 9 , 12 ], our results revealed high microbiological contamination of the water network, probably due to the long period of inactivity before the inauguration of the new pavilion. While Gram-negative bacteria and fungi tend to adhere to biofilms at or near distal points of use [ 3 , 8 , 24 ], Legionella can also colonize deep hospital infrastructures and is responsible for nosocomial cases of legionellosis [ 10 , 25 ]. Fortunately, as reported by some Authors [ 17 ], our remediation interventions (i.e., flushing with hydrogen peroxide and silver ions for 20 min/day for one week) resulted in an overall decrease in the bacterial load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies [ 9 , 12 ], our results revealed high microbiological contamination of the water network, probably due to the long period of inactivity before the inauguration of the new pavilion. While Gram-negative bacteria and fungi tend to adhere to biofilms at or near distal points of use [ 3 , 8 , 24 ], Legionella can also colonize deep hospital infrastructures and is responsible for nosocomial cases of legionellosis [ 10 , 25 ]. Fortunately, as reported by some Authors [ 17 ], our remediation interventions (i.e., flushing with hydrogen peroxide and silver ions for 20 min/day for one week) resulted in an overall decrease in the bacterial load.…”
Section: Discussionmentioning
confidence: 99%
“…31 of 2001 (Lgs.D.31/01) [ 1 ], are not always able to guarantee the safety of vulnerable patients [ 2 ]. Some hydrophilic microorganisms (e.g., Pseudomonas aeruginosa , Legionella , fungi) can cause serious infections if present in the water used to wash wounds, burns, medical devices and humidifiers, with the risk of an inauspicious outcome in patients with a high risk of infection [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant fungus isolated from the internal surfaces is probably related to a more humid internal environment. Humidity is an ideal condition for fungal proliferation, largely demonstrated both in foods [ 18 , 19 , 20 , 21 ] and indoor environments [ 22 , 23 , 24 , 25 ]. These data suggest the need to improve the safety of FVMs by applying proper maintenance, cleaning, and sanitization interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Candida species have been repeatedly isolated from all types of managed soils, including agricultural, orchards and vineyards, 35 trees and other plants 33,36,37 and compost 38 . In addition, yeasts are found in surface water or sediment from aquatic environments and polluted wetlands and in hospital potable water 39‐41 . Pathogenic yeasts are also found in dwellings, as illustrated with dishwashers and laundry machines, 42,43 and on vegetables, fruits and cheese 44,45 .…”
Section: The Environmental Sphere: Is Our Environment An Underestimat...mentioning
confidence: 99%